STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN DISIPLIN DAN PRESTASI SISWA - Riska Sya’ban; Riyanti Ismail (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The principal's leadership plays an important role in creating the school climate and enhancing students’ behavior and academic success. This research aimed to analyze the leadership strategies implemented by the principal of SMP Negeri 02 Marisa, including the previous leadership strategy, the rationale for the applying, the implementation of a new leadership strategy, and also its impact on students’ discipline and academic achievement. This study employed a descriptive quantitative research design using survey and percentage analysis techniques to obtain a comprehensive understanding of the phenomenon. The findings revealed that the previous leadership approach was relatively effective in maintaining organizational stability and keep the school align, however, it did not significantly improve students' understanding of discipline. In contrast, the newly implemented leadership strategy, which emphasized personal development through spiritual principles and inclusive decision-making within teams, received highly positive evaluations. The implementation of this strategy significantly enhanced students’ self-discipline, learning motivation, and academic success both inside and outside the classroom. Furthermore, the impact of the principal’s leadership was reflected in the school’s achievements at the national level, as SMP Negeri 02 Marisa was appointed as the Junior High School Ambassador of Gorontalo Province. These findings indicated that contextual and participatory leadership practices contribute significantly to enhance educational quality and promoting positive student accomplishment